HBM4EU - Deliverable Report D 5.5: Human biomonitoring in risk assessment: 2nd set of examples on the use of HBM in risk assessments of HBM4EU priority chemicals - Santonen, Tiina (2020)
Co-authors: Henriqueta Louro, Bruno Costa Gomes, Maria João Silva, Ricardo Assunção, Carla Martins, Paula Alvito (INSA)